Overcoming hesitancy to submit manuscripts for peer review - Tyler Prochnow; Bobbie L. Johannes; Ashley L. Merianos; Juanita-Dawne R. Bacsu; Matthew Lee Smith (New Prairie Press, 2023)
Publishing completed research is essential for knowledge dissemination and career advancement, yet many academics experience submission anxiety. Reasons include fear of rejection, imposter syndrome, and perfectionism. This commentary reviews drivers of submission hesitancy and outlines evidence-based strategies to empower manuscript submission. Consequences of delays are detrimental for individual productivity and scientific progress. Indicators of unhelpful rumination during endless revisions include excessive time re- reviewing background literature or endlessly analyzing data. Plagiarism angst can also stall submission. Strategies to promote manuscript submission include setting readiness checklists and timeline goals, seeking mentor perspectives on drafts, forming peer writing groups for accountability, understanding text reuse conventions, viewing peer input as collaborative, and reframing rejection as an expected part of review. While incentives must be reformed, mindset shifts can initiate positive norms amid existing pressures. Scientists have a responsibility to disseminate timely research and can implement techniques to do so.